A coloring tool for spiropyrans: solid state metal–organic complexation versus salification. Issue 33 (24th July 2019) - Seiler, Vanessa Kristina; Robeyns, Koen; Tumanov, Nikolay; Cinčić, Dominik; Wouters, Johan; Champagne, Benoit; Leyssens, Tom
Abstract : Controlling the type of merocyanine metal interaction for broad solid-state coloration. Abstract : In this work, we examine the nature of the spiropyran/merocyanine metal interaction in the solid state and highlight its various linking possibilities. A ring opening isomerisation of spiropyran results in the colored merocyanine, which is only rarely observed in the solid state. Introducing metal salts (ZnCl2, ZnBr2, and CoCl2 ) to four different spiropyran compounds ( i.e. 1, 3, 3-trimethylindolinobenzopyrylospiran, 1, 3, 3-trimethylindolino-β-naphthopyrylospiran, 1, 3, 3-trimethylindolino-8′-methoxybenzopyrylospiran, and 1, 3, 3-trimethylindolino-6′-nitrobenzopyrylospiran) leads successfully to the stabilisation of merocyanine. The ability to form different interactions as a complex, salt or a mixed form was discovered as well as the requirement of different synthetic pathways. Changing the solid form has a strong impact on the absorption properties, resulting in a tool which allows coloring of spiropyrans in the solid state covering a large scale spectrum from red to green.